Plants vs. zombies. 8, Lawn of doom part 2 - Tobin, Paul, 1965- (Spotlight ; Dark Horse Books, 2020)
Dr. Zomboss suffers his first defeat, but finds the deed to Halloween nonetheless. Desperate to keep Halloween safe, Nate challenges Dr. Zomboss to a series of contests with the deed as the ultimate prize.